2020
DOI: 10.1111/codi.15098
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of leakage in patients with handsewn vs stapled anastomosis after right hemicolectomy: a retrospective study

Abstract: Aim Anastomotic leakage is a major complication after right hemicolectomy leading to increased morbidity, mortality, length of stay and hospital costs. Previous studies have shown that the type of anastomosis (handsewn or stapled) is a major risk factor for anastomotic leakage. The purpose of this study was to evaluate the clinical impact of anastomotic leakage depending on the type of anastomotic technique (handsewn vs stapled). Method This was an observational, retrospective, crosssectional study. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
(41 reference statements)
0
19
1
1
Order By: Relevance
“…In the current study, the frequency of anastomotic leakage was higher in patients who underwent stapled end-to-end anastomosis than in those with handsewn or stapled sideto-end anastomosis. One previous report found that stapled anastomosis was associated with a significantly lower frequency of anastomotic leakage than handsewn anastomoses [18]; however, several recent reports on ileocolic anastomosis have identified a higher anastomotic leakage rate for stapled vs handsewn anastomoses [5,6,10,11,13]. Lee et al compared side-to-side and end-to-side anastomosis approaches in laparoscopic right hemicolectomy [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the frequency of anastomotic leakage was higher in patients who underwent stapled end-to-end anastomosis than in those with handsewn or stapled sideto-end anastomosis. One previous report found that stapled anastomosis was associated with a significantly lower frequency of anastomotic leakage than handsewn anastomoses [18]; however, several recent reports on ileocolic anastomosis have identified a higher anastomotic leakage rate for stapled vs handsewn anastomoses [5,6,10,11,13]. Lee et al compared side-to-side and end-to-side anastomosis approaches in laparoscopic right hemicolectomy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage is associated with mortality, short-and long-term morbidity, a potentially increased risk of recurrence, and poor prognosis [1,2]. The anastomotic leakage rate after right-sided colectomy is reported to range from 1.7 to 12% [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Oncological outcomes of laparoscopic resections for T4 colon cancer have not shown any significant difference between comparative observational studies and open surgery, although the risk of developing postoperative complications was significantly lower with a minimally invasive approach [1,2]. However, some multivisceral resections may be technically challenging.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Several risk factors have been identified for AL, including age, preoperative nutritional status, or laparoscopic approach [ 14 ]. Stapled anastomosis has been reported to present higher rates of clinically relevant AL [ 14 , 15 ], but without increasing either mortality or length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%